HISTORIOSOPHICAL AND ANTHROPOCENTRIC ASPECTS IN THE NOVELS BY YURIY KOSACH - Kurinna, Nataliia; Yurchak , Halyna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Purpose. The article deals with the novels by Yuriy Kosach in the context of historiosophical and anthropocentric issues of the European and national existentialism. The study is based on the little-known historical novels ​“The Rubicon of Khmelnytskyi” ​and ​“The Day of Wrath​”. Theoretical basis. Yuriy Kosach’s prose oeuvre is an impressive and original phenomenon of the Ukrainian creative writing. It greatly regenerated the Ukrainian fiction in worldview, problematic and thematic, genre and stylistic aspects, showing the concordance with the need to modernize national and European literary-aesthetic consciousness of the 20th c. The historical and adventure novels “The Rubicon of Khmelnytskyi” and “The Day of Wrath”, which present a person against the historical background, are particularly conspicuous in the aspect of artistic portrayal of historical events and figures. Kosach managed to integrally render the concept of a person, to apprehend the depth of its nature and multiplicity of senses of its existence, to reconsider the complexity of psychological filling of a person’s inner world, to present a broad view of the problem of relations between people, to originally substantiate his anthropological concept which is the embodiment of the “national code”. Originality. It traces the evolution of the word picture of B. Khmelnytskyi, which unfolds against the background of sociohistorical events and moral challenges. For the first time it has been proved that in his historical and adventure novels with the elements of philosophism (existential antejizm) and psychologism, the prose writer showed the specificity of forming the historic figure of Hetman as a wise European helmsman, a state-minded person, and a leader of the Ukrainians. Conclusions. It has been emphasized that Yuriy Kosach raised important psychological, historiosophic and ontological problems such as a human being and its existence, life and death, psychological splitting, fate and a person’s destiny, morality, national identity, struggle for own rights and freedoms, feeling of responsibility for others etc.